2009
DOI: 10.1007/s10856-009-3842-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in ac-impedance spectroscopy studies of normal human dentine: further investigations

Abstract: One of the age-related changes occurring in dentine structure is the formation of peritubular dentine on the inner walls of dentinal tubules leading to complete closure of tubules. Ac-impedance is safe, fast and non-invasive technique. In the last decade, the popularity of the technique has increased in dental research. Several investigators have used the technique to detect tooth cracks and caries. The results of in vitro studies showed that ac-impedance technique was more advanced for caries detection than v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…Age-related physicochemical changes of dentin are characterized by continuous deposition of peritubular dentin, consequent narrowing of the dentinal tubules, and a decrease in the number of dentinal tubules (3)(4)(5)(6). Several studies have shown that the number and diameter of dentinal tubules play an important role in the effectiveness of irrigation solutions and adhesion of root canal sealers as well as on the depth of bacterial invasion (4,7,8).…”
mentioning
confidence: 99%
“…Age-related physicochemical changes of dentin are characterized by continuous deposition of peritubular dentin, consequent narrowing of the dentinal tubules, and a decrease in the number of dentinal tubules (3)(4)(5)(6). Several studies have shown that the number and diameter of dentinal tubules play an important role in the effectiveness of irrigation solutions and adhesion of root canal sealers as well as on the depth of bacterial invasion (4,7,8).…”
mentioning
confidence: 99%
“…Especially when using ACIST, for instance, the age of the patients is of decisive importance to the interpretation of the results of measurement: the diameter of the dentinal tubuli decreases significantly with age through the apposition of peritubular dentine. The dentine therefore contains fewer electrically conductive electrolytes, resulting in an overall higher resistance [26,27]. Among young patients, on the other hand, the post eruptive enamel maturation represents a measurable independent variable [8,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Dentin is a complex hard tissue that comprises the bulk of the tooth and covers the dental pulp . Microtubules filled with dentinal fluid, odontoblastic process, mineralised intertubular dentin and highly mineralised peritubular dentin constitute the microstructure of dentin . With ageing, the thickness of the peritubular linings increase and reduction in the tubule lumen diameter begins .…”
Section: Introductionmentioning
confidence: 99%